2016
DOI: 10.1017/s0007123416000156
|View full text |Cite
|
Sign up to set email alerts
|

The Political Consequences of Gender in Social Networks

Abstract: Recent research on political discussion has focused on whether aspects of interaction create a ‘democratic dilemma’ for the mass public in which people face a choice between political participation and political tolerance. This article argues that there are important variations in how people react to their immediate social contacts. It explores this idea by studying how social disagreement and expertise interact with gender to explain variance in political participation. First, it shows that there are conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 65 publications
(107 reference statements)
0
13
0
Order By: Relevance
“…From our data, it appears technology access does not contribute to the gender gap in political engagement; rather, other psychological and social factors may lead women to use work technology for other purposes (Jackson, Ervin, Gardner & Schmitt, 2001;Poindexter, Meraz, & Weiss, 2008). Avoiding political content online, then, may have more to do with the inherent conflict in politics, and women tending to be higher than men on conflict avoidance (Brooks, 2010;Ulbig and Funk, 1999;Djupe, McClurg and Sokhey, 2016;Wolak and McDevitt, 2011). It is also possible women are accessing political information that does not conform to the knowledge battery included in the ANES but is policy or domain specific (Eveland & Hively, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our data, it appears technology access does not contribute to the gender gap in political engagement; rather, other psychological and social factors may lead women to use work technology for other purposes (Jackson, Ervin, Gardner & Schmitt, 2001;Poindexter, Meraz, & Weiss, 2008). Avoiding political content online, then, may have more to do with the inherent conflict in politics, and women tending to be higher than men on conflict avoidance (Brooks, 2010;Ulbig and Funk, 1999;Djupe, McClurg and Sokhey, 2016;Wolak and McDevitt, 2011). It is also possible women are accessing political information that does not conform to the knowledge battery included in the ANES but is policy or domain specific (Eveland & Hively, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Men are more likely than women to discuss politics (Huckfeldt & Sprague, 1995), express opinions (Atkeson & Rapoport, 2003), and try to influence others (Rapoport, 1981;Hansen, 1997). Men and women's discussion networks also look different from one another as men overwhelmingly discuss politics with other men (Djupe, McClurg, and Sokhey, 2016). Additionally, women are judged by others in their social networks to be less competent and politically knowledgeable (Huckfeldt & Sprague 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, her work did not consider gender differences. More recent research by Djupe, McClurg, and Sokhey (2016), which replicated her analysis, shows in some instances that women are less engaged in political activity as a response to hearing conflict, but not in others; they make the argument that more research is needed that considers how gender relates to negative political discussion. Indeed, more recent work suggests that it is not conflict avoidance among women, per se, but rather men's enjoyment of political arguments, that lead men to be more engaged in politics than women (Wolak 2020).…”
Section: Gender Masculinity and Civilitymentioning
confidence: 90%
“…Yet the information and values that shape individuals' decision whether to reward or punish the behavior of others are formed and disseminated through social interaction, which in turn unequivocally is gendered (Erickson 2006). Thus, drawing from the literatures on the gendered nature of social networks (McPherson and Smith-Lovin 1986;Molyneux 2002;Caiazza and Gault 2006;Erickson 2006;Norris and Inglehart 2006;Carpenter and Moore 2014;Djupe, McClurg, and Sokhey 2016), we expect to find a connection between the size of personal networks of evaluators and their gendered evaluations of women and men in positions of authority. We anticipate gender solidarity in leadership evaluation among women with larger networks, given that past scholarship has found that "women are more responsive to their networks than men" since their "subordinate position in our gender stratification system makes gendered issues more costly for women, and hence women are more attentive to information and influence on these topics" (Erickson 2006, 305).…”
Section: Introductionmentioning
confidence: 93%
“…Increasingly, research on behavioral differences between women and men identify the individual's personal and professional networks as critical sources of information and values (McPherson and Smith-Lovin 1986;Molyneux 2002;Caiazza and Gault 2006;Erickson 2006;Norris and Inglehart 2006;Carpenter and Moore 2014;Barnes 2016;Djupe, McClurg, and Sokhey 2016). In the workforce, networks matter enormously for the professional advancement of women precisely because individuals' ties vary in number and type by gender (Ibarra 1997;Campion and Shrum 2004).…”
Section: What Explains the Evaluation (And The Evaluators') Gender Gap?mentioning
confidence: 99%